Factors affecting on psychological health status of veteran’s spouses in Ilam city - Behzadifar, Meysam; Ahmadi, Nayeb Ali; Abdi, Shadi; Bahamin, Qobad; Shokouhi, Shabnam; Delpisheh, Ali (Advances in Nursing & Midwifery, 2017)
Abstract: Background and aim: With regard to the specific mental and physical health situation of veterans, their wives are dealing with peculiar stresses. The aim of the present study was to determine factors affecting on psychological health status of veteran’s spouses in Ilam city. Materials and Methods: This was a cross-sectional study. 111 veteran’s spouses of Ilam city were selected by random sampling in 2012. The veterans should have at least 25 percent injury. Data collection tools were general and economic forms and the General Health Questionnaire (GHQ). Data were analyzed with SPSS version 16 and using the t-test, Pearson correlation, logistic and multivariate regression. Findings: The mean of mental health score was 28.55 ± 14.63. The average mental health scores of cases with monthly income of 3000000-5999999, 6000000-8999999 and 9000000 Rial and more were 0.65, and 1.23 and 2.01 times of the group with income less than 3000000 Rial, respectively. Also, mental health in groups with education of secondary school, high school and college were 0.88, 1.77 and 2.87 times of the group with primary school education, respectively. The mental health has statistically significant correlation with both income and education (p<0.01). Age and social dysfunction had a direct and significant correlation with mental health (p=0.01 and r=0.3). Conclusion: Regular monitoring of mental health for veteran’s spouses is necessary. With respect to the type and percentage of injury, promotion of education levels and effective financial supports to families of veterans are essential steps to improve mental health indicators in the veteran’s spouses. Keywords: Mental health; Veterans; Factors